The Effect of the Heutagogy Methode on Improving Student Competence in the Heavy Equipment Technology Course among Automotive Engineering Education Students - Prima Idham Nugroho; Rafli Nazril Setiadi; Wahid Munawar (EDUJAVARE: International Journal of Educational Research, 2026)
Vocational higher education in Indonesia faces serious challenges in producing graduates who are both adaptive and competent in meeting the demands of Industry 4.0. This study aims to examine the relationship between the implementation of the heutagogy method and student competence in the Heavy Equipment Technology course within the Automotive Engineering Education Study Program. A quantitative correlational design was employed, involving 70 students as respondents. Data were collected through a five-point Likert scale questionnaire and analyzed using a series of statistical procedures, including validity testing, reliability testing, normality testing, and Spearman Rank correlation, with the aid of IBM SPSS Statistics. The validity test results demonstrated that all instrument items for both Variable X and Variable Y were declared valid, with r values ranging from 0.238 to 0.633 for Variable X and from 0.308 to 0.842 for Variable Y. Reliability analysis yielded a Cronbach's Alpha coefficient of 0.721 for Variable X and 0.846 for Variable Y, both of which satisfy the minimum reliability threshold required for research instruments. Given that neither variable followed a normal distribution as determined by the Shapiro-Wilk test, a nonparametric Spearman Rank correlation was applied. The analysis produced a correlation coefficient of r_s = 0.666, significant at the 0.01 level, indicating a strong and positive relationship between the two variables. These findings confirm that greater intensity in the implementation of the heutagogy method throughout the learning process is associated with higher levels of student competence in the Heavy Equipment Technology course.